Intrapopulation variation in the diet of franciscana dolphin (Pontoporia blainvillei) off southern Brazil. (25th May 2021) - Bassoi, Manuela; Secchi, Eduardo R.; Danilewicz, Daniel; Moreno, Ignacio B.; Santos, Roberta A.; Shepherd, John G.
Abstract: The franciscana dolphin ( Pontoporia blainvillei ) is a coastal dolphin endemic to the western South Atlantic Ocean. The dolphin is listed as vulnerable in the IUCN Red List, with incidental catches in gillnet fisheries the greatest conservation concern for this species. Insights into the feeding habits of this dolphin are essential to understand its distribution, movements and use of habitat, which are fundamental for effective management of the species. The feeding habits of franciscana dolphins were investigated from analyses of stomach contents of animals incidentally caught by two fishing operations from southern and northern regions of the southern Brazilian coast. In this study we investigate the existence of intrapopulation (sexual maturity and sex-related) variation in the diet of the franciscana dolphin, evaluating the spatial (northern and southern geographic areas) and seasonal influences. The analyses were based on Linear and Generalized Linear Models (LM and GLM). The majority of identified prey species were bottom-dwelling teleosts and the squid Doryteuthis sanpaulensis . The most important prey differed spatially and seasonally between northern and southern regions of the study area, and our results revealed significant differences between sexes and sexual maturity stages, mainly related to prey species sizes. This variation might indicate differences in prey selection, availability or habitat use patterns among these groups. In any case, these dietary differences are likely to minimize intraspecific competition for food resources, and/or indicate spatio-temporal variation in prey availability.